Negative emotion can be “more negative” for those with high metacognitive abilities when problem-solving - Hong, Seok-sung; Bae, Jinhee; Son, Lisa K.; Kim, Kyungil (Frontiers in Psychology, 2023)
Metacognitive monitoring ability enables you to learn things and solve problems better by making you find and carry out an appropriate strategy. In the aspect of emotions, those who have high monitoring ability are known to allocate more cognitive resources to perception and control of negative emotions than those with low metacognitive ability. Though monitoring of emotions can help reduce negative emotion by enabling efficient control, it may interrupt the use of a strategy for problem-solving by preventing sufficient cognitive resources from being allocated when performing a cognitive task. To confirm this, we divided the participants into groups with high and low monitoring abilities and, after arousing their positive/negative emotions, checked of using an appropriate problem-solving strategy with the Cognitive Reflection Test (CRT). As a result, those who have a high-monitoring ability were shown to use more efficient problem-solving strategy than those who have a low monitoring ability in a situation where there was no interference of emotions and also when positive emotion was aroused. However, when negative emotion was aroused, the CRT scores of high monitoring ability were significantly lower than those of when positive emotion was aroused. In particular, the CRT scores of high monitoring ability group dropped as low as low those of monitoring ability. Also, we found that metacognitive monitoring ability, when interacted with emotion, indirectly affected the CRT score, and that monitoring and control affected by emotion were mediated in the process.